Detecting potential community fish refuges (CFRs) of southeast Cambodia and assessing their vulnerability - Vo, M. Q.; Truong, Q. C.; Vuong, S. T. (International Water Management Institute, 2024)
This study investigates water dynamics and identifies potential Community Fish Refuges (CFRs) in Cambodia's Prey Veng and Svay Rieng provinces using multi-year satellite imagery (2018–2023), GIS data, and field data. The analysis focuses on stable surface water regions and their suitability for CFR establishment to support aquatic biodiversity and community livelihoods.